Anti-VEGF-resistant subretinal fluid is associated with better vision and reduced risk of macular atrophy. Issue 11 (26th May 2021) - Zarbin, Marco A; Hill, Lauren; Maunz, Andreas; Gliem, Martin; Stoilov, Ivaylo
Abstract : Background/aim: To evaluate relationships between subretinal fluid (SRF), macular atrophy (MA) and visual outcomes in ranibizumab-treated neovascular age-related macular degeneration (nAMD). Methods: This post hoc HARBOR trial (NCT00891735 ) analysis included ranibizumab-treated (0.5 or 2.0 mg, monthly or as-needed, all treatment arms pooled) eyes with nAMD and baseline (screening, baseline and week 1) SRF. SRF presence, SRF thickness (0, >0–50, >50–100 and >100 µm) and subretinal fluid volume (SRFV) were determined by spectral domain optical coherence tomography (SD-OCT). Best-corrected visual acuity (BCVA) was assessed. MA was identified using fluorescein angiograms and colour fundus photographs, as well as SD-OCT. Results: Seven hundred eighty-five of 1097 eyes met analysis criteria. In eyes without baseline MA, residual versus no SRF at month (M) 3 was associated with lower MA rates at M12 (5.1% vs 22.1%) and M24 (13.3% vs 31.2%) (both p<0.0001); MA percentages at M12/M24 were similar among patients with residual SRF at M6. Higher baseline SRFV was associated with a lower MA rate. Greater mean BCVA was observed with residual SRF of any thickness (>0–50 µm, 71.2 letters; >50–100 µm, 71.3 letters; >100 µm, 69.2 letters) versus no SRF (63.6 letters), but the change in BCVA from baseline to M12 or M24 was the same for eyes with or without treatment-resistant subretinal fluid (TR-SRF) at M3 or M6. Conclusion: TR-SRF was not detrimental to vision outcomes over 2 years, regardless of thickness. MA rates were significantly higher without TR-SRF.